The Origin and Understanding of the Incretin Concept - Rehfeld, Jens F. (Frontiers in Endocrinology, 2018)
Gastrointestinal hormones that stimulate insulin secretion at physiological concentrations are incretins. This concept has recently attracted considerable attention in the wake of drugs developed from the gut hormone GLP-1 (glucagon-like peptide-1) for diabetes therapy. But the renewed enthusiasm has also restricted the concept to just two hormones, GLP-1 and GIP (glucose-dependent insulinotropic polypeptide). The purpose of the present overview is two-fold: First to tell that the incretin concept is far from new. It has a more than a century long history full of ups and downs. Second, that the incretin concept may now have become too narrow. Thus, it is likely that incretin comprises additional gastrointestinal hormones, which interact with GIP and GLP-1 during normal meals containing protein, fat and complex carbohydrates (and not just pure glucose). Such broader incretin concept may stimulate development of novel gut hormone-derived drugs.